Therapists Behind Bars: Criminalizing Gay‐to‐Straight Conversion Therapy. (8th February 2021) - Taglienti, James
Abstract : Conversion therapy is a practice used to "change" an individual's sexual orientation from homosexual to heterosexual. Parents who expose their child to conversion therapy drastically increase the child's likelihood of developing anxiety, depression and self‐destructive behavior. Currently, 18 states ban mental health professionals from conducting conversion therapy. However, in those states, if a mental health professional conducts the therapy, the penalty is only a relatively small fine for unprofessional conduct. Additionally, to report their therapist, victims must file a complaint, which poses difficulties for minors. This Note proposes a criminal statute for mental health professionals who conduct conversion therapy. Key Points for the Family Court Community: Roughly 100, 000 minors will be subjected to LGB conversion therapy before turning 18. Minors who are subjected to conversion therapy are five‐times more likely to attempt suicide than their peers. LGB youth who are rejected by their families are eight‐times more likely to develop anxiety, depression, and suicidal ideation, and six‐times more likely to use illegal drugs. Conversion therapy amplifies the shame and rejection LGB youth already experience growing up, leading to self‐hatred.